role of liver /kiudney microsomal antibody type 1 with type 2-autoimmune hepatitis - Al- obeidy, Eman sh.; Al- Mousawy, khalida; hasso, maan, G.; FATADH, MAKKI- H. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: